Theoretical issues of accounting of biological assets and problems of its application in practice - Ravshanov Alisher Babakulovich, (THE INNOVATION ECONOMY, 2026)
In the practice of financial accounting, “biological assets” are recognized as an important object of financial accounting and reporting. Correct classification and accounting of biological assets additionally improve the quality of financial reporting. In the article, the author gives scientific definitions of the concepts of biological assets, and also presents problems and solutions related to their accounting.